The Munasabah Between Surah Al-Mulk and Surah Al-Qalam and Its Relationship to Character Education from the Perspective of Wahbah al-Zuhaylī - Amir Faishol Fath; Dia Hidayati Usman; Muhammad Modassir Ali (ZAD Al-Mufassirin, 2026)
This study aims to analyze the correlation (munāsabah) between Surah Al-Mulk and Surah Al-Qalam and its relevance to character education from the perspective of Wahbah al-Zuhaylī. The research employs a qualitative method with a library research approach. Data were collected from classical and contemporary tafsir literature, especially Tafsir Al-Munir by Wahbah al-Zuhaylī. The findings reveal a strong thematic continuity between Surah Al-Mulk, which emphasizes divine sovereignty and spiritual awareness, and Surah Al-Qalam, which highlights moral development and the exemplary character of Prophet Muhammad (peace be upon him). This correlation indicates that tawhidic awareness (tawḥīd) serves as the foundation for character building. According to Wahbah al-Zuhaylī, character education is rooted in values of faith, morality, patience, and integrity.